Tobacco control policy analysis in China : economics and health - Hu, Teh-wei (Series on contemporary China ;, 2008)
This is the first book that analyzes tobacco control policies in China from the perspectives of economics and health. For readers interested in the economic aspects of tobacco control policy issues not only in China but also in other developing countries, this book provides a comprehensive analytical and empirical framework addressing key debated issues. This book covers a range of interesting topics from the prevalence of smoking in China, health and economic burden of smoking in China, demand for cigarettes and taxation in China, the role of tobacco on farming, the tobacco industry and the World Trade Organization, poverty and smoking in China, to future challenges of tobacco control for the Chinese government.